Parasternal intercostal muscle activity during methacholine‐induced bronchoconstriction. Issue 4 (14th March 2017) - MacBean, Victoria; Pringle, Claire L.; Lunt, Alan C.; Sharp, Keith D.; Ali, Ashraf; Greenough, Anne; Moxham, John; Rafferty, Gerrard F.
Abstract : New Findings: What is the central question of this study? The parasternal intercostal electromyogram (EMGpara) is known to provide an accurate, non‐invasive index of respiratory load–capacity balance. Although relationships between EMGpara and both airflow obstruction and hyperinflation have been shown, the independent contribution of each factor has not been examined. What is the main finding and its importance? Reductions in airway calibre and inspiratory capacity along with increases in EMGpara were induced via methacholine challenge. A strong inverse relationship was observed between EMGpara and airway obstruction, with no influence of inspiratory capacity. These data suggest that EMGpara is more strongly influenced by airway calibre than by changes in end‐expiratory lung volume during airway challenge testing. Neural respiratory drive, measured via the parasternal intercostal electromyogram (EMGpara), provides a non‐invasive index of the load–capacity balance of the respiratory muscle pump. Previous studies in patients with obstructive lung disease have shown strong relationships between EMGpara and the extent of both airflow obstruction and hyperinflation. The relative influence of the two factors has not, however, been described. Airflow obstruction was induced via methacholine challenge testing in 25 adult humans. Forced expiratory volume in 1 s (FEV1 ) and surface EMGpara during tidal breathing were measured after each dose, with 20 of the participants also undergoing measurements of inspiratory capacity (IC) at each stage. Linear mixed model analysis was used to assess dose‐wise changes in FEV1 and EMGpara, and thereafter to determine the influence of changes in FEV1 and IC on change in EMGpara. Median (interquartile range) FEV1 decreased significantly [from 96.00 (80.00–122.30) to 67.80 (37.98–92.27)% predicted, P < 0.0001] and EMGpara increased significantly [from 5.37 (2.25–8.92) to 6.27 (3.37–19.60) μV, P < 0.0001] from baseline to end of test. Linear mixed model analysis showed a significant interaction between methacholine dose and induced change in EMGpara, with an increase in EMGpara of 0.24 (95% confidence interval 0.11–0.37) μV per methacholine dose 2 . Change in FEV1 further influenced this relationship [increase in slope of 0.002 (0.004–0.001) μV dose −2 per % predicted fall in FEV1, P = 0.011], but not with change in IC. These data suggest that bronchoconstriction exerts a more potent influence on levels of EMGpara than changes in end‐expiratory lung volume during methacholine challenge. Abstract :